Electroretinographic Findings in a Patient with Congenital Stationary Night Blindness Due to a Novel NYX Mutation. (September 2013) - McAnany, J. Jason; Alexander, Kenneth R.; Kumar, Nalin M.; Ying, Hongyu; Anastasakis, Anastasios; Fishman, Gerald A.
ABSTRACT Purpose: To document a novel NYX gene mutation in a patient with X-linked complete congenital stationary night blindness and to describe this patient's electroretinogram (ERG) characteristics. Methods: ERGs were recorded from a 17-year-old male with a previously unreported NYX mutation (819G > A) that results in a missense codon change (Trp237Ter). ERGs were recorded in response to brief-flash stimuli, 6.33-Hz sawtooth flicker, and sinusoidal flicker ranging from 6.33–100 Hz. The omitted stimulus response (OSR) of the flicker ERG, which is thought to be generated within the ON-pathway, was also assessed. Results: The patient's single-flash responses were consistent with previously documented NYX ERG characteristics, including a high-luminance flash response that was electronegative under dark-adapted conditions and a square-like a-wave followed by an abnormally shaped positive potential under light-adapted conditions, both of which are consistent with an ON-pathway deficit. Further evidence for an ON-pathway deficit included: (1) ERGs to rapid-on sawtooth flicker in which b-wave amplitude was reduced more than a-wave amplitude, and (2) responses to sinusoidal flicker that lacked the normal amplitude minimum and phase inflection near 12 Hz, ERG characteristics that are like those of patients with other NYX mutations. Novel findings included a pronounced amplitude attenuation for sinusoidal flicker at frequencies above approximately 50 Hz and an absent OSR, suggesting ON-pathway dysfunction at high frequencies. Conclusion: The substantial loss of ERG amplitude and apparent ON-pathway dysfunction at high temporal frequencies distinguish this patient with a Trp237Ter NYX mutation from those with other previously reported NYX mutations.